Evaluation of genetic variability and trait association for yield improvement of Lentil - Khanam, M; Kabiraj, MS; Rashid, MM; Raffi, SA (Progressive Agriculture, 2022)
Lentil is a nutritious food and one of the world's oldest domesticated legumes. The present studyevaluatedthe nature and magnitude of variability, heritability, genetic advance and association among the yield and yield contributing traits in 24 lentils (Lens culinaris M.) genotypes. From the 13 traits considered, phenotypic coefficients of variation (PCV) were found higher than genotypic coefficient of variation (GCV) which indicates less effect of the environment for the expression of traits studied. Seed weight per plants demonstrated the highest PCV and GCV (60.26 & 59.87) followed by number of seeds per plant (49.14 & 48.97) and number of pods per plant (48.58 & 47.95, respectively). Most of the traits showed high heritability as days to maturity exhibited the highest heritability (99.96%) followed by number of seeds per plant (99.33%). Genetic advance as percent of mean was higher for seed weight per plant (122.58%) and number of seeds per plant (100.56%). Among the traits, number of seeds per plant (0.95& 0.94) and number of pods per plant (0.94 & 0.92) showed positive and significant correlation with seed weight per plant at both phenotypic and genotypic correlation. Consequently, path analysis revealed positive and direct effect of number of pods per plant (0.310&372) and number of seeds per plant (0.770&0.659) on seed weight per plant in both genotypic and phenotypic level, respectively. Based on the genetic analysis of 13 characters, number of pods per plant, number of seeds per plant,1000-seed weight and seed weight per plant were found as the most superior traits can be used in hybridization program for the development of high yielding lentil genotypes. Progressive Agriculture 32 (2): 107-116, 2021